Assessment of surgical outcomes of femtosecond laser-assisted in situ keratomileusis in patients with low compliance to postoperative follow-up: a retrospective observational study in a tertiary hospital in China. Issue 11 (2nd December 2018) - Zhang, Qing; Wang, Jing; Li, Mohan; Ding, Xiaohu; Tao, Liming
Abstract : Objectives: Poor follow-up after femtosecond laser-assisted in situ keratomileusis (FS-LASIK) is common in general clinical practice. We aimed to assess the surgical outcomes of patients with poor compliance to FS-LASIK follow-up but who returned to the clinic with additional prompting at a 1-year visit. We also compared their surgical outcomes with those of patients who returned unprompted. Design: Retrospective and observational study. Setting: An urban tertiary hospital in China. Participants: We reviewed the medical records of myopic patients who underwent binocular FS-LASIK. These patients were all recommended, but not compulsively required, to return for termly postoperative examinations including measurement of uncorrected distance visual acuity (UDVA), refraction and assessment of complications. According to records of follow-up visits, 1009 eligible patients were categorised as follows: (1) 124 who returned unprompted at the 1-year visit (group 1) and (2) 885 lost to follow-up at the 1-year visit. We randomly selected and called back 105 (group 2) out of the 885 patients for an extra postoperative examination. Results: At the 1-year visit, the visual outcomes of the two groups of patients were comparable. No differences in postoperative UDVA were found between the two groups (−0.02±0.06 logarithm of the minimum angle of resolution (logMAR) and −0.02±0.05 logMAR for groups 1 and 2, respectively, p=0.175). Patients in group 2 showed greater hyperopic dioptres than patients in group 1 (0.37±0.59 D vs −0.29±0.69, p<0.0001). No vision-threatening complications were observed in either group of patients. Conclusions: The visual and refractive outcomes of patients who were lost to follow-up after FS-LASIK surgery were good and comparable to those who returned unprompted. The results indicated that rigorous postoperative follow-up may be unnecessary in general clinical practice, except for patients who are at a high risk for postoperative complications.